National archaeological museum of Naples quick guide - Cappelli, Rosanna (Soprintendenza Archeologica Di Napoli e Caserta, 1999)
This is an essential guide to the "masterpieces" which must be seen, to the new displays in the Museum, and to the history of the Collections. It is a quick and scholarly guide to one of the most extraordinary archaeological collections in the world. There are exhibitions of Egyptian, Italic, Magna Graecian and Roman artefacts as well as the very famous collection of antiquities from Pompeii and Herculaneum.